Unraveling the Causal Effects of Risk Factors on Diabetes Mellitus Insights from Mendelian Randomization Studies - Manaswi Chigurupati (North American Journal of Engineering Research, 2025)
Diabetes mellitus (DM) is a growing public health issue globally, with incidence having risen markedly over the past decades. Traditional observational studies have identified numerous risk factors; however, confounding and reverse causation restrict firm causal inferences. Mendelian randomization (MR) is a powerful genetic epidemiological technique intended to avoid these biases. This review meta-analyzes MR studies designed to determine causal risk factors for type 2 diabetes mellitus (T2DM), which have identified key metabolic, cardiovascular, behavioral, inflammatory, and genetic determinants. Causal factors identified include obesity, triglycerides, systemic inflammation, and hypertension, while protective relationships are identified for physical activity and improved sleep quality. In addition, MR studies refute earlier hypotheses, demonstrating the absence of causal associations for lipoprotein(a), adiponectin, and C-reactive protein. Future research studies should focus on improving genetic instruments and investigating populations from diverse backgrounds to enhance causal inference. Such evidence is crucial for guiding targeted intervention programs and precision medicine approaches to reducing the global burden of diabetes.